The role of skill enhancing trade in Brazil: some evidence from microdata - Bruno Cesar Araújo; Francesco Bogliacino; Marco Vivarelli (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Brazil was characterised by a marked process of trade liberalisation in the ‘90s, resulting in a dramatic increase in the volumes of exports and imports since the year 2000.Over the same period, the relative demand for skilled labour has increased substantially. To investigate whether these two simultaneous phenomena are linked is the purpose of this paper. More in particular, this study focuses on the impact of trade openness and technology transfer on the relative demand for skilled labour in Brazilian manufacturing firms, using a unique panel database (resulting from merging three different statistical sources) of Brazilian manufacturing firms over the period 1997-2005. Descriptive statistics show that the increase in the relative demand for skilled labour was mainly driven by the within-industry variation, supporting the hypothesis that technology (and in particular technological transfer from richer countries) may have played a role in determining the skill-upgrading of Brazilian manufacturing firms. The econometric results further support this hypothesis. Indeed, the estimations show that domestic capital is a complement of the skilled workers and that imported capital goods clearly act as a skill-enhancing component of trade. Hence, our results support the view that embodied technological change through the importation of capital goods has involved a clear skill-biased impact in Brazilian manufacturing.
Keywords: O33; O54; F16; 330; Skill-Enhancing Trade; Skill-bias; Panel Data; Brazil; Außenhandelsliberalisierung; Technologietransfer; Industriegüteraußenhandel; Qualifikation; Arbeitsnachfrage; Facharbeiter; Brasilien